Multiple Steady State Equilibria of Job Composition - Anton Abdulbasah Kamil; MOHD NAIN HJ. AWANG (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2010)
In this paper we construct an example of multiplicity to further illustrate the general equilibriumforces at work. We assume that good and bad jobs produce inputs that are perfect substitutes, onlythat there is a quality difference. This will accentuate the tendency toward multiplicity and enable toexplicitly construct two equilibria.